Science Content Knowledge of Pre-Service Teachers in Biology Elementary School Level - Rif'at Shafwatul Anam (Universitas Pendidikan Ganesha, 2022)
Expectations for qualified primary school teachers in Indonesia are very high. The public is aware that education in elementary schools is an essential part of introducing a scientific discipline to students, one of which is science. To provide optimal science learning, teachers must have qualified Science Content Knowledge (SCK) so that students have no misconceptions and confusion. This study aims to analyze the mastery of prospective SCK teachers on biology subjects at the elementary level. The research method in this study is a descriptive method using a survey design. Data were obtained from 284 primary school teacher education program participants at the end of the semester. The instrument is a multiple-choice test with four answer choices with 40 questions. The device was then given to the participants and analyzed by calculating the percentage and putting it into a predetermined category. This study found that the mastery of pre-service teacher SCK needs to be considered because the average category of understanding is in the